Detection of VUV photons with large-area avalanche photodiodes - Monteiro, C. M. B. (2005)
The room-temperature response of large-area avalanche photodiodes (LAAPDs) to 128- and 172-nm light pulses is investigated. The minimum detectable number of photons, which can produce a signal just above the noise level, is found to be around 1300 and 600 photons, respectively. The LAAPD relative statistical fluctuations in the detection of 15 000 photons of 128 nm and 25 500 photons of 172 nm were found to be about 3.9% and 2.2%, respectively. Both the minimum detectable number of photons and statistical fluctuations do not depend on the photon wavelength, but rather on the number of charge carriers produced by the light pulse in the LAAPD. For these light levels, good LAAPD performance is already achieved for gains as low as 30 to 60.